Empowering leadership workshop - Kang, Mei Feng (2025)
PEKAN, 4 January 2025 - Mandarin Language Society (MLS) of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has successfully organized a one-day Leadership Workshop on 4 January 2025 at Dewan Kuliah Utama, Centre for Modern Languages, UMPSA Pekan. The program was held to enhance leadership skills, organizational management, and social etiquette among participants, fostering better collaboration among society members. This workshop was attended by 35 participants from Gambang and Pekan campuses. The event focused on sharing valuable insights on club and program management, financial planning, entrepreneurship, and effective communication in multimedia and social media.